Analysis of Indonesian Language Errors in the Hidden Novel - Yanti, Dewi; Mubarok, Yasir; Silmi Syafina, Laila; Jayatri, Putri (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
This research aims to describe the form of the misuse of Indonesian language errors in Hidden (2022) novel. This study utilized a qualitative method. Data was collected using document analysis. This study utilized data from the Hidden novel, which was published on Wattpad in 2022. The error analysis process involves data collection, error identification, error classification, error quantification, and error cause/source analysis. The results of this study show that there are several language errors in The Hidden novel on Wattpad. There are three types of errors: phonological errors (14%), syntactic errors (67%), and morphological errors (19%). First, errors at the phonological level which include errors in omission of phonemes. Second, errors in the syntactic level which included errors in the use of punctuation, the use of redundant words, parallel structure errors, unclear sentences, and spelling errors. Finally, errors at the morphological level which include errors in the use of the affixes di-, affixes -ke, and the use of affixes se-